Case Report: Multiple Seizures After a Diphenoxylate-Atropine Overdose in a Small Child - Wang, Chun-Hui; Song, Li-Jia; Yang, Yang; Qu, Xiao-Peng; Lan, Li; Liu, Bei (Frontiers in Pharmacology, 2021)
Poisoning is a type of accidental injury and it is considered a major public health problem worldwide. Oral drug poisoning in children is an important cause of accidental injury and even death. It is a common critical emergency in the field of pediatrics. Once a child unintentionally takes an overdose, regardless of whether it caused poisoning or not, they should be admitted to the hospital for emergency treatment. Acute poisoning in children most frequently occurs through the digestive tract. Drug poisoning can happen in children of all ages. In children younger than 1 year, drug poisoning is mostly caused by the parents during feeding, while in children aged 1–3 years, it predominantly occurs as a result of an accident. A case of diagnosis and treatment of a child with diphenoxylate-atropine poisoning is reported herein. The early manifestation of this child was acute toxic encephalopathy with clinical manifestations of a coma, convulsions, and respiratory depression. A brain MRI showed extensive damage to the bilateral caudate nucleus, lenticular nucleus, parietal lobe, precuneus lobe, and occipital lobe. Accidental administration of a large dose of diphenoxylate results in severe clinical symptoms and can cause obvious diffuse brain damage.